Study of the effect of ultraviolet radiation on the development of corona discharge in high voltage networks - D. V. Petrov; R. E. Berezhnoy; I. T. Frantsuzov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. One of the significant components of losses in high-voltage electrical networks is corona discharge losses or "corona losses", which can, depending on the voltage level of the power line and weather conditions, reach 50 % or higher of the total loss level. A significant factor that increases corona losses is solar ultraviolet radiation. Goal. To investigate the effect of the ultraviolet radiation spectrum on the corona discharge ignition voltage. Materials and methods. The research is based on analytical, experimental and statistical methods. Results and discussion. The influence of weather factors on the corona ignition voltage and, as a result, on coronary losses is significant. At the same time, only precipitation or drizzle are considered as factors that increase coronary losses, without taking into account the influence of ultraviolet radiation. The conducted experimental studies confirm the hypothesis of the effect of ultraviolet radiation on the ignition voltage of the corona discharge and, ultimately, on an increase in coronary losses. Conclusion. Corona losses in high-voltage networks increase significantly under ultraviolet irradiation. Thus, when calculating coronary losses in high-voltage networks, it is necessary to take into account a two- to three-fold increase in losses in hours with a high ultraviolet index.